2015
DOI: 10.1186/s12985-015-0281-9
|View full text |Cite
|
Sign up to set email alerts
|

Dried blood spots PCR assays to screen congenital cytomegalovirus infection: a meta-analysis

Abstract: The performance of dried blood spots (DBS) polymerase chain reaction (PCR) assays in screening for congenital cytomegalovirus (cCMV) infection varies between different studies. To determine whether the DBS PCR assay has sufficient accuracy to be used as a screening test for cCMV infection, we performed a meta-analysis of 15 studies (n = 26007 neonates) that evaluated the performance of DBS PCR tests in screening for cCMV infection and that met our inclusion criteria. The pooled sensitivity and specificity were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 37 publications
1
37
0
2
Order By: Relevance
“…cCMV‐positive was defined as a positive result in both the screening and confirmation test. The polymerase chain reactions had an assumed sensitivity of 84%, which was the pooled sensitivity in a recently published systematic review, since the analytical sensitivity of the used polymerase chain reactions of one to five copies per reaction and the input of 15 μL or 50 μL was comparable to the best performing assays in this review.…”
Section: Methodsmentioning
confidence: 90%
“…cCMV‐positive was defined as a positive result in both the screening and confirmation test. The polymerase chain reactions had an assumed sensitivity of 84%, which was the pooled sensitivity in a recently published systematic review, since the analytical sensitivity of the used polymerase chain reactions of one to five copies per reaction and the input of 15 μL or 50 μL was comparable to the best performing assays in this review.…”
Section: Methodsmentioning
confidence: 90%
“…Alternative approaches to cCMV diagnosis at a later date by using archived neonatal dried blood spot (DBS) polymerase chain reaction testing may be an appropriate testing strategy for infants with hearing loss, depending on the sensitivity of the DBS assay used and length of storage of DBS neonatal Guthrie cards. 25,26 Identification of asymptomatic CMV-positive children provides opportunities for focused surveillance. Fowler and others have shown that cCMV positive infants are at risk for delayed onset, fluctuating, and progressive SNHL.…”
Section: Discussionmentioning
confidence: 99%
“…Studies reporting detection of CMV from DBS have already been performed [6,7,12,16,17,18,19]. However, methods reporting the highest sensitivities for CMV DNA detection from DBS are not suitable for high-throughput screening being labor intensive and not cost effective.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 15 studies ( n = 26,007 neonates) has evaluated the performance of DBS real-time polymerase chain reaction (PCR) tests in screening for CCMV infection showing a better sensitivity. The rates of detection of CMV DNA in DBSs from symptomatic and asymptomatic neonates were similar, 95.90 and 96.67%, respectively [16]. …”
Section: Introductionmentioning
confidence: 99%